Sixty-four new records for the flora of Peru from rapid biological inventories in the Peruvian Amazon - Torres Montenegro, Luis A. (2019)
Between 2000 and 2016 we carried out 15 rapid biological inventories in remote areas of the Andean foothills and Amazon basin in Peru. During these inventories, 27 botanists collected 9397 fertile vascular plant specimens. By the end of 2017, more than half of these specimens had been identified to species. Of the 2303 species identified to date, 64 species and 2 genera (Dicorynia and Monopteryx) are new records for the flora of Peru. If this rate of discovery proves typical, the number of new records for Peru in the rapid inventory material could increase, which indicates that there is still much to discover in the Peruvian flora.